2003
DOI: 10.1128/jb.185.16.5023-5026.2003
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Lactobacillus pentosus d -Lactate Dehydrogenase to a d -Hydroxyisocaproate Dehydrogenase through a Single Amino Acid Replacement

Abstract: , respectively, at the final step of anaerobic glycolysis, concomitantly oxidizing NADH into NAD ϩ (16). Lactic acid bacteria possess at least one of the two types of LDHs, fermenting the corresponding stereoisomer of lactic acid (12). In spite of the similarity in their catalytic reactions, the two types of enzymes are evolutionally separate from each other, belonging to distinct protein superfamilies (4,21,33). D-LDHs share a common protein structure not only with various D-2-hydroxyacid dehydrogenases (2,4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…NADH Binding to D-LDHs-The dissociation constants (K D ) of N97D D-LDH and NADH were determined essentially according to a previous report (38). The binding of NADH to the D-LDHs was followed as the change in NADH fluorescence intensity (⌬F) essentially according to the method used for L-LDHs (39), with excitation and emission wavelengths of 340 and 460 nm, respectively, using a Jasco FP-750 spectrofluorophotometer.…”
Section: Crystallographic Analysis Of N97d D-ldh-mentioning
confidence: 99%
See 2 more Smart Citations
“…NADH Binding to D-LDHs-The dissociation constants (K D ) of N97D D-LDH and NADH were determined essentially according to a previous report (38). The binding of NADH to the D-LDHs was followed as the change in NADH fluorescence intensity (⌬F) essentially according to the method used for L-LDHs (39), with excitation and emission wavelengths of 340 and 460 nm, respectively, using a Jasco FP-750 spectrofluorophotometer.…”
Section: Crystallographic Analysis Of N97d D-ldh-mentioning
confidence: 99%
“…⌬F was determined by comparing the fluorescence intensities of NADH in the presence and absence of the enzymes (15 M) at 30°C in 50 mM sodium MES buffer (pH 6.0). The K D values for the enzymes with NADH were calculated according to the procedure for L-LDHs (38,39) by curve fitting with Kaleidagraph. (Fig.…”
Section: Crystallographic Analysis Of N97d D-ldh-mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that only minor structural changes, such as amino acid replacements, cause drastic change, in the enzyme function in this family, as for example, conversions from a D-lactate dehydrogenase (D-LDH) to a D-hydroxyisocaproate dehydrogenase (D-HicDH), 17,18) and even from a formate dehydrogenase to a D-2-HydDH. [19][20][21] Although the enzymes in this family generally exhibit strict specificity toward NAD, it was reported recently that Holoferax mediterranei D-2-HydDH, which belongs to the D-2-HydDH family, utilizes both NAD and NADP as coenzymes, acting on bulky 2-ketoacid substrates.…”
mentioning
confidence: 99%
“…[21][22][23][24] In spite of the great variety of their catalytic functions, however, there is no reported enzyme in the D-2-HydDH family that exhibits high catalytic activity toward C3-branched substrates. 17,18,22,25) Enzymes purified from Lactobacillus curvatus, 26) Enterococcus faecalis, 27,28) and also the yeast Rhodotorula graminis 29) are known to catalyze efficiently the conversion between benzoylformate (C 6 H 5 -CO-COO À ) and D-mandelate (C 6 H 5 -CHOH-COO À ), which possess a branched side chain at the C3 position, and are called D-mandelate dehydrogenases (D-ManDHs). Nevertheless, their structural relation to the D-2-HydDH family remains uncertain, because little is known about the protein structure of D-ManDHs.…”
mentioning
confidence: 99%